Meningkatkan Hasil Belajar Pak Menggunakan Metode PBL Materi Aku Tumbuh Dan Berkembang Kelas III SDN 16 Sungai Jelawai - Silfanus Silfanus (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
. The background to this research emerged because of problems in increasing students' interest and understanding of learning material. Students tend to feel bored and sleepy during the learning process, which leads to low learning outcomes. To overcome this challenge, interesting learning methods are needed to improve learning outcomes and student interest in class. One method that has been proven effective is Problem Based Learning (PBL). The aim of this research is to improve student learning outcomes and achieve learning achievement targets in class. The research method used is quantitative. The results of the first cycle showed that 4 students were at the advanced level, 4 students were at the proficient level, and 2 students were at the appropriate level, with an average observation learning result of 78%. In the second cycle, there was a significant increase with 6 advanced level students, 3 proficient level students, and 1 decent level student, and the average observation learning result reached 86.5%. The implications of these findings confirm that the PBL method is able to improve learning outcomes and student achievement targets in learning.